The egg and I - MacDonald, Betty Bard (London Hammond & Company, 1946)
Relates the joys and frustrations of life on a poultry farm in the mountains of Washington
'First impression, July, 1945 ... Fifteenth impression, March, 1946.'
Keywords: Farm life